2013
DOI: 10.1111/jmi.12079
|View full text |Cite
|
Sign up to set email alerts
|

Determining the fibrillar orientation of bast fibres with polarized light microscopy: the modified Herzog test (red plate test) explained

Abstract: The identification of bast fibre samples, in particular, bast fibres used in textiles, is an important issue in archaeology, criminology and other scientific fields. One of the characteristic features of bast fibres is their fibrillar orientation, referred to as Z- or S twist (or alternatively right- and left-handed fibres). An empirical test for determining the fibrillar orientation using polarized light microscopy has been known in the community for many years. It is referred to as the modified Herzog test o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 17 publications
2
40
0
Order By: Relevance
“…Fibre is nettle. At α = 45° zero-order grey is clearly observed, which proves the expected positive sign of elongation[16] The modified Herzog test performed on (a) nettle (S-twist) and (b) jute (Z-twist). To the left the sample orientation angle α ≈ 0°, to the right the sample orientation angle α ≈ 90°[16] …”
supporting
confidence: 53%
See 1 more Smart Citation
“…Fibre is nettle. At α = 45° zero-order grey is clearly observed, which proves the expected positive sign of elongation[16] The modified Herzog test performed on (a) nettle (S-twist) and (b) jute (Z-twist). To the left the sample orientation angle α ≈ 0°, to the right the sample orientation angle α ≈ 90°[16] …”
supporting
confidence: 53%
“…Recent studies by Haugan and Holst [16] developed theoretical model for distinguishing natural fibres like jute, nettle, cotton, etc. and found that the fibril structure and their angle is different for all fibres based on polarised microscopic views and birefringence results.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…In recent years, there has been an increased interest in the scientific identification of archaeological and historical plant fibre material (see, e.g., Bergfjord et al . ; Haugan and Holst , ; Skoglund et al . ; Lukešová ; Lukešová et al .…”
Section: Introductionmentioning
confidence: 99%
“…Cotton, the most prominent textile plant in modern times, only became available in Europe at a much later date. Furthermore, cotton is not a bast fibre and can easily be distinguished from bast fibres using a polarization microscope (Luniak , Haugan and Holst ).…”
Section: Introductionmentioning
confidence: 99%
“…The modified Herzog test, originally developed by Herzog (Herzog ), is described in several places in the literature (Luniak ; Herzog ; Goodway ; Petraco and Kubik ). A detailed description together with the first analytical model of the method was recently presented by the authors of this paper (Haugan and Holst ). X‐ray micro‐diffraction can be used to identify ancient fibres.…”
Section: Introductionmentioning
confidence: 99%